Quantum error correction using quantum convolutional neural network - Mishu, Niloy Deb Roy; Meem, Fatema Islam; Ridwan, A. E. M; Rahman, Mohammad Mushfiqur; Mary, Mekhala Mariam (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.